Abdominal Lymphonodular Cryptococcosis in an Immunocompetent Child - Mehjabeen Zaidi; Sonia Qureshi; Sadia Shakoor; Saira Fatima; Fatima Mir (Case Reports in Pediatrics)
We describe our experience with an apparently immunocompetent child presenting with pyrexia of unknown origin without focal signs. Investigations revealed lymphadenopathy at lung hila, mesentery, and porta hepatis. The child had received at least two months of empiric antituberculous therapy (ATT) before she came to us. A CT-guided biopsy revealed granulomatous inflammation. PAS stain showed yeasts which stained blue with Alcian blue, suggesting C. neoformans.